USO DAS METODOLOGIAS ATIVAS NO ENSINO DA LÍNGUA INGLESA: UM ESTUDO DE CASO - SILVA, RENATO RODRIGUES DA (2020)
Currently we are inserted in a society in which it is highlighted that the traditional education no longer complies with the demands of the students. We present as a proposal the use of the Active Methodologies and the Hybrid Teaching, understood in this study as the blend of presencial and online teaching. In this research, it is proposed the applicability of the Active Methodology in the Teaching of the English Language in a free course school located in São Caetano do Sul - SP, with the participation of three teachers. Afterwards, the narratives of these three teachers will be analyzed in order to verify the results of the Active Methodology in the classroom. The hypothesis sustaining this work is that the Active Methodology and the Hybrid Teaching can contribute to the teaching-learning process of the English language and to the autonomy of the student. We have three objectives: (i) discuss the concepts of Education and active methodologies and how they can potencialize the teaching-learning process; (ii) Present the methods and approaches of the English language and its impact in the non-formal educational (iii) analyze the main concepts of the active methodologies according to the what the three English teachers narrated. The justification of this research comes from the need of the educator to transform his didatics in class. The corpus selected for this study will be three interviews of the selected teacher for this research. The theoretical basis for this work are the studies about Active Methodology by Filatro and Cavalcanti (2018), Mattar (2017), Bacich and Moran (2018); the researches about case Studies by Gil (1995), Ventura (2007) and Yin (2011); and the investigations about English teaching by e Almeida Filho (1993), Richards and Rodgers (2001) and Vilson Leffa (2016). The methodology used is empirical based on the case studies and the method is inductive from case study. As results, we conclude that the teachers believe to be teaching an active class when they are only exploring the pillars of the Active Methodology in a superficial way.